استراتيجية تعليم مهارة الكتابة لطلاب الصف الثامن في مدرسة المحروس الثانوية الإسلامية الأهلية ميدان - Shofi Khairani; Taufiq, Muhammad (Shaut al Arabiyyah, 2024)
The maharah kitabah teaching strategy is a way of arranging learning steps before delivering the material. Maharah kitabah has the ability to communicate human thoughts and ideas regularly in written form. This research focuses on teaching strategies and factors of difficulty for students in studying the Maharah Kitabah. The aim of this research is to find out the teaching strategies applied to students in learning Maharah Kitabah and to find out the factors that make it difficult for students to understand Arabic writing. This research uses a descriptive qualitative method because the researcher’s aims and objectives are to find out and describe a problem that exists in the school. Based on the researchers’ findings, the maharah kitabah teaching strategy used by Arabic teachers is the basic strategy for writing Arabic letters, namely khatt, the teacher must first introduce the rules for writing Arabic letters correctly, including writing letters that cannot be interrupted and written one by one, starting from the next At the right level, students must be able to read written Arabic. Apart from that, the difficulty factor for students in understanding the Maharah Kitabah is that almost all of the students in this madrasa come from elementary school. When learning Arabic, teachers have to start learning from the basics because many students do not know the procedure for writing Arabic letters. However, some students have an MI educational background so they no longer experience difficulties in understanding the basics of writing Arabic, another factor is the lack of motivation and support from the students’ parents in learning Arabic. By implementing basic teaching strategies through the khatt learning aspect, it is easier for students to understand subsequent Arabic language material.